Seven Acantholaimus (Chromadoridae: Nematoda) species from one deep-sea sediment sample (Angola Basin, south-east Atlantic) - Miljutina, M. A.; Miljutin, D. M.; Tchesunov, A. V. (Journal of the Marine Biological Association of the United Kingdom, 2013)
The genus Acantholaimus (Chromadoridae: Nematoda) is one of the most species-rich deep-sea nematode genera. The descriptions of two new species and supplemental descriptions of five known species from the Angola Basin (south-east Atlantic Ocean) and a depth of about 5500 m are given. Acantholaimus formosus sp. nov. is characterized by a spindleshaped body with narrow elongated anterior end, the position of amphideal fovea on the apical tip of the body and by robust rugae and onchia. Acantholaimus skukinae sp. nov. is characterized by its cylindrical body shape; short outer labial, cephalic, cervical, and somatic setae; large amphideal fovea; the position of its amphideal fovea (situated relatively far from the head end); and relatively small onchia. Acantholaimus angustus was previously found in the Peru Basin (central-eastern Pacific) and the Clarion–Clipperton Nodule Province (Equatorial Pacific), about 13,000 km apart from the nearest previous location of finding. The type location of A. verscheldi is the Kenyan coast of the Indian Ocean. New specimens of this species were found about 8000 km apart from the type location. Acantholaimus akvavitus, A. iubilus and A. quintus were previously found in different parts of the Atlantic and the Pacific.
first published online 19 July 2012